TINJAUAN YURIDIS AKIBAT HUKUM ADANYA UNSUR PENIPUAN DALAM PERJANJIAN UTANG PIUTANG - Zikriatul Aini; M. Yazid Fathoni (Private Law, 2023)
This study aims to determine the legal consequences if there is an element of fraud in the debt agreement and how the judge considers in deciding the case in decision no. 4 PK/Pid/2019. This type of research is normative research, with the approach method used being the statutory approach (Statue Approach), conceptual approach (Conceptual Approach), and analytical approach (Analytical Approach). Based on the research results, this case has legal consequences, namely Erni Saroinsong was proven to have committed fraud and was sentenced to 2 (two) years in prison, and the debt agreement between Erni Saroinsong and Robert Thoenesia can be requested for cancellation following Article 1328 of the Civil Code.